ANALYSIS OF THE EFFECT OF FINANCIAL RATIO ON BANKING PERFORMANCE IN INDONESIA STOCK EXCHANGE WITH STOCK RETURN AS A MODERATING VARIABLE IN 2013-2017 - Siregar, Lasrini (International Journal of Public Budgeting, Accounting and Finance, 2019)
The purpose of this study was to determine the effect of financial ratios on banking performance on the Indonesia Stock Exchange with stock returns as moderating variables for 2013-2017. The population in this study are all banking companies that have been publicly listed on the Indonesia Stock Exchange, with the period 2013-2017. Based on sample selection techniques, a total sample of 21 banking companies was listed on the Indonesia Stock Exchange in the 2013-2017 research period. This study uses secondary data, namely quantitative data obtained from the Indonesia Stock Exchange website. The results of the study are simultaneously and partially concluded that the independent variables (CAR, BOPO, NIM, NPL, LDR) have a significant effect of 29.8% on the dependent variable Y (ROA). Moderating test results show that the 5 independent variables have a significant effect on company size as a moderating variable and then, Return asset as a moderating variable has a significant effect on the relationship between independent variables on the dependent variable. In other words, company size is proven as a moderating variable that influences the relationship of independent variables with dependent variables. The conclusion is that there is an effect of the financial ratio on banking performance on the Indonesia Stock Exchange with stock return as a moderating variable for 2013-2017. It is suggested to the next researcher to examine the banking sector from various other financial aspects that affect financial performance. For companies it is recommended to pay attention to determining the optimal capital structure, positive company growth, and profitability to improve financial performance.